Legal Protection and Liability for Pet Abuse that Happens in Indonesia - Maharani, Diva Alya (Jurnal Scientia Indonesia, 2020)
The increasing number of cases of animal abuse at this time makes many opinions that realize that enforcement of animal protection is getting more lax and does not strictly maintain and treat according to the law in real life. However, it's not just the abuse of farm animals but also that pets are on the rise in rates of human-made abuse and death. The rise of this case creates unrest for people who also have pets. In this case, the public hopes that it can be reaffirmed by the apparatus and the law in Indonesia as the comfort and security of the community is an obligation for State assistants to fulfill it. This study aims to find out how the regulation regarding maintenance focuses on pets in Indonesia and how to protect and guarantee the welfare of pets and what are the laws that apply to perpetrators of pet abuse in Indonesia.